Pengaruh Kepemimpinan Kepala Sekolah, Budaya Kerja dan Kepuasan Kerja Terhadap Kinerja Guru di Yayasan Pendidikan Mutiara Baru Bekasi - Yustina Ambarini; Siregar, Edi (Jurnal Satya Mandiri Manajemen dan Bisnis, 2017)
The Purpose of the research is to findout whether there is a positive and significant Influence of headmaster leadership, work culture and job satisfaction toards teacher performance of Yayasan Pendidikan Mutiara Baru Bekasi. Based on the relevant theoretical research, hypothesis exposed are; (1) Is there positive and significant influence of headmaster leadership towards teacher performance? (2) Is there positive and significant influence of work culture towards teacher performance? (3) Is there positive and significant influence of job satisfaction towards teacher performance? (4) Is there positive and significant together of headmaster leadership, work culture and job satisfaction towards teacher performance? Research Results prove that there is the influence of Principle leadership, culture of work and job satisfaction significantly on the performance of the teachers of Yayasan Pendidikan Mutiara Baru Bekasi.principle leadership is the variables that affect the performance of the teachers.